MANAGEMENT AND PATTERNS OF CULTURAL INHERITANCE IN INDONESIA - Acep Iwan Saidi; Setiawan Sabana; Nia Kurniasih (Jurnal Sosioteknologi, 2017)
This study titled Management and Patterns of Cultural Inheritance in Indonesia puts Bali as the scope of area of this case study. To be more specific, the object of this study is limited to the phenomena that occur in relation to wood-based handicrafts as one of the activities which are based on creativity deemed most prominent among the Balinese community. The study was conducted using ethnography as a method of data collection, followed by a study based on the perspective of culture. This study has obtained some interesting findings, such as Balinese crafts was originally a creative effort of the community based on the integration of nature, culture, and religion. Unequal inheritance patterns in term of technical skills and insight deepening about the values established by the integration of the three elements of the craft has led the development of Balinese crafts towards the growth of the character of "craft workers", not a craft culture.